LIGHTWEIGHT CONCRETES BASED ON POROUS AGGREGATES - Abdurahimov Abdukarim Abduhalimzoda (American Journals, 2022)
Structural elements used in construction are required to serve for a long time, without losing their strength, integrity and serviceability under the influence of external forces without risk. The article envisages improving the properties of lightweight and fine-grained concrete and expanding its use in construction work.
Keywords: light, porous, filler, strong, artificial, expanded clay, agloparite, composition.